THE ROLE OF THE NURSE IN THE CARE OF NEPHROLOGY PATIENTS AND THE IMPORTANCE OF TRAINING IN THIS FIELD - Bara, Rajmonda (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to observe the role of nursing in the care of nephrology patients and the importance of their training in this field.This study is a retrospective descriptive type.In this study included a total of 160 licensed nurses with an average age of 41.5 ± 12.63 years.The study was conducted in a period of 2013-2015 in several regional hospitals in the country.The data were analyzed and certain conclusions drawn by SPSS version 15.00.The value p <0.05 was considered statistically significant.Tables and graphs are used for data visualization160 nurses obtained from the study showed that the average age was 41.5 ± 12.63 years.Noticed a predominance of women 102 (3.75%) compared with 58 men (36.25%).The study shows that 43 (26.88%) of individuals have continuing nursing care training versus 117 (73.13%) of individuals who do not have this training.The study shows that 117 individuals or 73.13% participate in workshops on continuing nursing management versus 43 individuals or 26.88% who do not participate in these continuing nursing care trainings.t = 0.206 indicating that there is no statistically significant difference between the two variables.P = 0.01. On the basis of the distribution of time nursing spends in treating patients with nephrologic problems we obtain the followingresults:Hemodialysis 19.3 or 20%.Peritoneal dialysis 12.57 or 13%, Management of chronic renal disease 19.03 or 20%, Continuous renal replacement therapy 7.1 or 8%, Acute care 22.55 or 21%.Overall nephrology 14 or 15%.The data collected showed that there are specific aspects of SRK in patient management that put out that nurses had an extremely heavy role in assessing, monitoring and health education and it needed improvement continuous training and their certification